Engaging EFL learners in online peer feedback on writing: What does it tell us? - Saeed M.A.; Ghazali K.; Sahuri S.S.; Abdulrab M. (Informing Science Institute, 2024)
Aim/Purpose The current case study aimed to investigate the engagement of nine English as foreign language (EFL) learners in online peer feedback on writing in a Facebook group. Specifically, the study focused on the issues of writing addressed in peer feedback and the learners' perception of peer feedback in the Facebook group. Background Peer feedback on writing has attracted the attention of many researchers and in-structors of writing in English as second/foreign language (ESL/EFL) contexts. More recently, the application of synchronous and asynchronous technologies, including Facebook, has been reported to foster ESL/EFL learners' engagement in peer feedback. Yet, in the EFL university context, the teacher/instructor still represents the sole resource of feedback, while learners are only passive receivers of feedback. Therefore, it is necessary to encourage EFL learners to be providers of feedback by engaging them in peer work in writing. Methodology The study was conducted among nine EFL Arab learners beyond the university writing course. As an extension to enhance their writing in the Facebook group, the activities of peer feedback reported in this study were monitored by the course instructor for three months. The learners' interactional feedback exchang-es, text revisions, and written reflections were qualitatively analyzed and the pat-terns of interaction were quantified. Contribution The findings contribute to the previous body of knowledge about the role of peer feedback, as well as the application of how asynchronous technological tools such as Facebook facilitate learners' interactional feedback exchanges in writing. Findings The learners engaged in interactional feedback exchanges in the revision-oriented discourse (n=1100 (64%)). These comments triggered global text revisions focus-ing on content, organization, and argumentative genre (n=533 (31%)) and local text revisions focusing on language and mechanics/conventions (n=567 (33%)). The learners also engaged in the non-revision-oriented discourse (n=620 (36%)) that focused on establishing group cohesion in terms of a friendly social context, social support, socialization, social ties, and attachment among them. The learners also perceived the Facebook group as an interactive learning environment that facilitates their peer feedback on writing beyond the university context. Recommendations for Practitioners The findings of the current study underlie useful pedagogical implications for EFL instructors and lecturers as well university students, specifically how peer feedback can be used by instructors as a way to enhance learners' writing skills. Moreover, with the increasing access to social networks such as Facebook groups, EFL learners can engage themselves in peer feedback activities beyond the uni-versity writing courses for further development in writing. Recommendation for Researchers Significant insights on EFL learning may be gleaned from analysing peer feedback on learning activities, which are easily facilitated by commonly available social networks such as Facebook. Hence, researchers who are interested in this domain are encouraged to look beyond the traditional teaching medium. Impact on Society The use of social networks (including Facebook groups) for educational purposes has received much attention from university learners worldwide. This research can facilitate people's awareness of the value of such networks in creating learning opportunities outside the university context. Future Research Future research could combine both synchronous and asynchronous technologies in peer feedback and focus on the effect of peer feedback on each learner's writing.